Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1093/cercor/bhad224
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry and network-based atrophy patterns in SCN1A-related Dravet syndrome

Abstract: Mutations of the voltage-gated sodium channel SCN1A gene (MIM#182389) are among the most clinically relevant epilepsy-related genetic mutations and present variable phenotypes, from the milder genetic epilepsy with febrile seizures plus to Dravet syndrome, a severe developmental and epileptic encephalopathy. Qualitative neuroimaging studies have identified malformations of cortical development in some patients and mild atrophic changes, partially confirmed by quantitative studies. Precise correlations between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
2
1
Order By: Relevance
“…Lack of information does not allow discerning whether MRI was not performed or unrevealing, leaving open the possibility that a systematic analysis in a large cohort, ideally by applying morphometric methods, might reveal a common pattern of abnormality, despite nonspecific qualitative findings. 25,26 Dysmorphisms, described in 69% of previously published patients, were observed in only 25% of those included in this report, and no recognizable recurrent pattern could be identified in this and previous studies. However, mild dysmorphisms in a rare condition are easily underreported, as they may escape recognition if patients are not seen by expert clinical geneticists and are reported via an international collaboration in which each center contributes single or very few observations, making interindividual comparison impossible.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Lack of information does not allow discerning whether MRI was not performed or unrevealing, leaving open the possibility that a systematic analysis in a large cohort, ideally by applying morphometric methods, might reveal a common pattern of abnormality, despite nonspecific qualitative findings. 25,26 Dysmorphisms, described in 69% of previously published patients, were observed in only 25% of those included in this report, and no recognizable recurrent pattern could be identified in this and previous studies. However, mild dysmorphisms in a rare condition are easily underreported, as they may escape recognition if patients are not seen by expert clinical geneticists and are reported via an international collaboration in which each center contributes single or very few observations, making interindividual comparison impossible.…”
Section: Discussioncontrasting
confidence: 59%
“…Variable brain MRI alterations, not suggesting a recurrent pattern of abnormality, were identified in 17% of our patients (4/24, 17%) and in 27% (4/15, 27%) of those previously reported, for whom, however, this information was not available in 38%. Lack of information does not allow discerning whether MRI was not performed or unrevealing, leaving open the possibility that a systematic analysis in a large cohort, ideally by applying morphometric methods, might reveal a common pattern of abnormality, despite nonspecific qualitative findings 25,26 …”
Section: Discussionmentioning
confidence: 99%
“…Studies exploring quantitative sub eld alterations in TLE reported an overall effect of temporal lobe seizures manifesting as bilateral medial hippocampal atrophy, and a more selective effect of hippocampal seizures, leading to disease-proportional CA1 atrophy [50,51]. The hippocampal formation acts as an epicenter of more intense structural changes even in epilepsy syndromes in which no clear indication of seizure genesis in the hippocampus exists, such as SCN1A-related Dravet syndrome [52] and idiopathic generalized epilepsy syndromes [20,53]. In a previous study of PCDH19-related encephalopathy, we demonstrated altered gyri cation in the parahippocampal and entorhinal regions, and diffusion abnormalities in the underlying white matter (Lenge et al, 2020), but no alterations emerged in the hippocampus when it was examined as a whole.…”
Section: Discussionmentioning
confidence: 99%